The growth of Shannon : the impact of economic change on a country town : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Tannock, J. L. McC (Massey University, 1968)
It was the aim of this study to arrive at a better understanding of the present functions and morphology of a small New Zealand country town through an examination of the principal economic processes of its past. It is apparent from this investigation that there has been a close relationship between intensity of economic activity and growth-rate. Furthermore, the nature of the economic activities affected the kind of development which took place. In addition, it was found that the changing functions necessitated by fluctuating economic forces left residuals which are not only a key to the past but also influence the present character of the town. Although it shares many of the characteristics of other small North Island towns the unusual nature of its past has bestowed a certain individuality on Shannon.
Keywords: Shannon, New Zealand; History; Economic conditions